Kontroversi Dalam Media Youtube: Analisis Penafsiran Gus Baha Dan Ustaz Adi Hidayat Tentang Kisah Nabi Adam - Amalia, Lubna Harira; Asshdiqi, Ahmad Fajri (Sunan Kalijaga Islamic State University, 2024)
This research is motivated by the lack of understanding among some members of society regarding the diversity of interpretations, particularly in the story of Adam and Eve's expulsion from paradise, which is often perceived as their fault. The study focuses on two prominent Indonesian scholars, Ustaz Adi Hidayat and Gus Baha. From the various discussions by these two figures on the story of Prophet Adam, this research is limited to videos from three YouTube channels: Adi Hidayat Official, Tafsir NU, and Ngaji Gus Baha Jogja. The aim of this research is to analyze the controversies surrounding the interpretation of the story of Prophet Adam between Ustaz Adi Hidayat and Gus Baha, as well as to understand the ideological constructs presented in these discourses. The research uses a qualitative approach based on a literature study, with primary data obtained from the videos on these three YouTube channels. The analysis of the study employs Norman Fairclough's critical discourse theory, encompassing textual aspects, discourse practice (analysis of the YouTube accounts), and sociocultural practice (external factors influencing interpretation). The results reveal two main controversies: first, the interpretation related to the angels in Surah Al-Baqarah [2]: 30; second, the interpretation regarding the expulsion of Adam and Eve from paradise. Additionally, there are differences in how the story is presented. Gus Baha tends to use a philological approach, while Ustaz Adi Hidayat focuses more on linguistic studies. The analysis of the YouTube accounts indicates that Tafsir NU and Ngaji Gus Baha Jogja tend to support Nahdlatul Ulama, which is based on ahlus sunnah wal jamaah, whereas Adi Hidayat Official leans towards Muhammadiyah, which does not adhere to a single imam. Thus, Gus Baha clearly supports ahlus sunnah wal jamaah, while Ustaz Adi Hidayat does not associate his interpretation with any particular manhaj.